Niche wars : Australia in Afghanistan and Iraq, 2001-2014 - Blaxland, John Charles, 1963-; Fielding, Marcus; Gellerfy, Thea (Australian National University Press, 2020)
Australia invoked the ANZUS Alliance following the Al Qaeda attacks in the United States on 11 September 2001. But unlike the calls to arms at the onset of the world wars, Australia decided to make only carefully calibrated force contributions in support of the US-led coalition campaigns in Afghanistan and Iraq. Why is this so? Niche Wars examines Australia's experience on military operations in Afghanistan and Iraq from 2001 to 2014. These operations saw over 40 Australian soldiers killed and hundreds wounded. But the toll since has been greater. For Afghanistan and Iraq the costs are hard to measure. Why were these forces deployed? What role did Australia play in shaping the strategy and determining the outcome? How effective were they? Why is so little known about Australia's involvement in these campaigns? What lessons can be learned from this experience? Niche Wars commences with a scene-setting overview of Australia's military involvement in the Middle East over more than a century. It then draws on unique insights from many angles, across a spectrum of men and women, ranging from key Australian decision makers, practitioners and observers. The book includes a wide range of perspectives in chapters written by federal government ministers, departmental secretaries, service commanders, task force commanders, sailors, soldiers, airmen and women, international aid workers, diplomats, police, journalists, coalition observers and academics. Niche Wars makes for compelling reading but also stands as a reference work on how and why Australia became entangled in these conflicts that had devastating consequences. If lessons can be learned from history about how Australia uses its military forces, this book is where to find them. -- From publisher's website.